Metabolism and Antiretroviral Activity of Tenofovir Alafenamide in CD4+ T-Cells and Macrophages from Demographically Diverse Donors. Issue 7 (October 2014) - Bam, Rujuta A; Birkus, Gabriel; Babusis, Darius; Cihlar, Tomas; Yant, Stephen R
Background: Tenofovir alafenamide (TAF) is a novel investigational prodrug of tenofovir (TFV) that permits enhanced delivery of TFV into peripheral blood mono-nuclear cells (PBMCs) and lymphatic tissues. A critical step in the intracellular metabolic activation of TAF is mediated by the lysosomal protease cathepsin A (CatA). Here, we investigated CatA levels together with intracellular metabolism and antiretroviral activity of TAF in primary CD4 + T-lymphocytes (CD4s) and monocyte-derived macrophages (MDMs) isolated from a demographically diverse group of blood donors. Methods: CD4s and MDMs were prepared from fresh PBMCs. CatA levels were quantified in cell extracts by monitoring TAF hydrolysis using HPLC. Intracellular TAF metabolites were quantified by HPLC combined with mass spectrometry. Antiviral activities in activated CD4s and MDMs were determined using HIV-1 single-cycle reporter and p24 antigen production assays, respectively. Results: The levels of CatA and intracellular TAF metabolites differed minimally in CD4s and MDMs among 13 tested donors. TAF was >600-fold and 80-fold more potent than parent TFV in CD4s and MDMs, respectively, and its relative range of antiviral activity across all tested donors was comparable to that of other HIV-1 reverse transcriptase inhibitors, with mean ±sd (range) EC50 values of 11.0 ±3.4 (6.6–19.9) nM and 9.7 ±4.6 (2.5–15.7) nM in CD4s and MDMs, respectively. Conclusions: These results indicate consistent intracellular metabolism and antiretroviral potency of TAF in relevant target cells of HIV-1 infection across multiple donors of variable gender, age and ethnicity, supporting further clinical investigation of TAF.